2014
DOI: 10.2174/0929867321666140304105526
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Tryptophan Metabolism in Cardiovascular Disease

Abstract: Atherosclerosis (AS), a major pathologic consequence of obesity, is the main etiological factor of cardiovascular disease (CVD), which is the most common cause of death in the western world. A systemic chronic low grade immune-mediated inflammation (scLGI) is substantially implicated in AS and its consequences. In particular, pro-inflammatory cytokines play a major role, with Th1-type cytokine interferon-γ (IFN-γ) being a key mediator. Among various other molecular and cellular effects, IFN- γ activates the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 75 publications
(77 reference statements)
4
71
0
1
Order By: Relevance
“…However, due the poor performance of antioxidant strategies in limiting atherosclerosis and cardiovascular events, it remains to be answered if oxidative modification is causal for the initiation or is an injurious response to atherogenesis [96] . Disease underlying interactions are too complex and the understanding is too fragmentary that clear, reliable therapeutic recommendations can be given [101] . The strong interconnection of metabolic and inflammatory pathways suggests that metabolically induced inflammatory processes should be considered as early, or even primary events [171] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due the poor performance of antioxidant strategies in limiting atherosclerosis and cardiovascular events, it remains to be answered if oxidative modification is causal for the initiation or is an injurious response to atherogenesis [96] . Disease underlying interactions are too complex and the understanding is too fragmentary that clear, reliable therapeutic recommendations can be given [101] . The strong interconnection of metabolic and inflammatory pathways suggests that metabolically induced inflammatory processes should be considered as early, or even primary events [171] .…”
Section: Resultsmentioning
confidence: 99%
“…In this context, e.g., neopterin is a useful indicator of the immune activation status and oxidative stress [6] and Kyn/ Trp ratio accounts for aspects of immunoregulation via IDO and represents an important metabolic checkpoint. Normalization of tryptophan metabolism represents an important goal to improve the outcome of patients suffering from CVD, whereby treatments with IDO inhibitors such as 1-methyl tryptophan could be considered [101] . However, IDO is well known for its immunosuppressive properties, and its inhibition by medications may also lead to adverse effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kynurenine is a metabolite of tryptophan degradation, and previous studies (23,24) suggested that the Kyn/Trp ratio could be a potent indirect indicator of indoleamine 2,3-dioxygenase (IDO), a rate-limiting enzyme of tryptophan catabolism. This pathway is induced by proinflammatory cytokines, especially interleukin-2, TNF-␣, and interferon-␥ (24).…”
Section: E743mentioning
confidence: 99%
“…Catabolites in the Kyn pathway of Trp catabolism are important for regulating the immune system and inflammation 10, 11. Emerging evidence also indicates that these catabolites play significant roles in cardiovascular pathophysiology 12, 13, 14…”
Section: Introductionmentioning
confidence: 99%